Tanfid Wasilah At-Ta'lim Al-Qur'an Al-Arabi Corpus Fi Ta'lim Al-Lugah Al-Arabiyah Li Tullab As-Saff Al-Hadi Asyar Fi Ma'had Tahfidzul Qur’an Ayatul Mubarak - Arti, Arum Tri Budi; Ahkas, Akmal Walad (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This study discusses the implementation of the learning media The Qur’anic Arabic Corpus in Arabic language instruction for Grade XI students at MA Ponpes Tahfidzul Qur’an Ayatul Mubarak. The Qur’anic Arabic Corpus is a web-based platform that provides morphological and syntactic analysis of Qur’anic texts, offering a contextual and Qur’an-based Arabic learning experience. It can serve as teaching material for learning grammatical structures within Qur’anic verses. The purpose of this study is to determine the effectiveness and role of The Qur’anic Arabic Corpus as a learning medium in enhancing students’ understanding of Arabic grammar rules, particularly in the areas of nahwu (syntax) and sharaf (morphology), as well as to identify the challenges encountered during the implementation process. The research method employed is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study show that the implementation of The Qur’anic Arabic Corpus has a positive role in the learning process and provides a significant impact. Students became more enthusiastic, engaged, and better able to understand the grammatical structures of Qur’anic verses. This medium also aids teachers in delivering material in a visual and interactive manner. Challenges encountered include limited technological proficiency and the English-language interface, which can be overcome through guidance, as well as students' insufficient foundational knowledge in nahwu and sharaf, and limited instructional time.Thus, based on the findings above, The Qur’anic Arabic Corpus can be considered an effective alternative modern learning medium for Arabic language education, particularly within Qur’an memorization-focused Islamic boarding schools (pesantren tahfidz).